A new egg parasitoid for possible biological control of the asiatic maize borer in Malaysia - Hussein, Mohd Yusof; Yahya, H. J.; Schiltuzen, M. (Universiti Putra Malaysia Press, 1996)
A species of egg parasitoid tentatively identified as Trichogramma papilionis Nag. was found attacking egg masses of Ostrinia furnacalis Guenee. The life cycle of the parasitoid was completed within 9 days; the egg, larval and pupal stages lastedfor 2,4 and 3 days, respectively. The female: male sex ratio was 3:1, higher than the usual 2:1 sex ratio for Trichogramma spp. Superparasitism was observed whereby 3 individuals were produced from one . host egg. All eggs were parasitized in 4 days at 2:1 (host: parasitoid) ratio. The female parasitoid showed a high degree of searching efficiency and normally parasitized all eggs in a batch before continuing her search for the next egg batch. The female spent 40% of the time searching on the upper surface of a maize leaf, 30% on the lower surface and 30% on the leaf edges. The female searching and parasitization behaviour followed the Type III functional response curve. The female parasitoid showed positive response to the odour ofthe maize leaf, indicating a possibility that a kairomone or contact communication chemical is involved. T. papilionis appeared to be a very efficient egg parasitoid of O. furnacalis and a good candidate for a biological control programme of the pest.